Pengaruh Kompensasi Terhadap Prestasi Kerja Pada PT Garuda Agung Kencana - Gede Tresna Adi Putra; I Wayan Bagia (Universitas Pendidikan Ganesha, 2020)
This study aims to influence the compensation on work performance at PT. Garuda Agung Kencana. The research design used in this study is causal quantitative. The subjects of this study were all employees of PT. Garuda Agung Kencana The object of this study focuses on the variables of compensation and work performance. The population of this study was 55 people. Data collection was performed by questionnaire method, which was then analyzed by simple linear regression. The results obtained in this study indicate that compensation has a positive and significant effect on work performance at PT. Garuda Agung Kencana by 64.6%